Kinerja Badan Permusyawaratan Desa Dalam Pemerintahan di Desa Patukuki Kecamatan Peling Tengah Kabupaten Banggai Kepulauan - Risky, Moh.; Nasrullah; Tawil, Yulizar Pramudika (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The lack of understanding among BPD members regarding their duties and functions can affect the performance of the organization itself. This research aims to describe the performance of the Village Consultative Body in carrying out its governmental functions in Patukuki Village. The approach used in this research is qualitative. The research was conducted in Patukuki Village, Peling Tengah District, Banggai Islands Regency. Data was obtained from various sources, namely the village head, BPD Chairperson, BPD Secretary, hamlet figures, and community representatives. Data collection techniques include observation, interviews, and documentation. The data analysis process was carried out step by step, starting from collection, reduction, data presentation, to drawing conclusions and data verification. The research results show the low understanding of BPD members regarding their duties, weak coordination with the village government, and lack of community participation. The quality of service is quite good, but follow-up on aspirations is still minimal. The productivity and responsiveness of the BPD need to be improved through training and closer cooperation with the community. In terms of responsibility, the BPD has carried out its duties according to regulations, but inter-agency cooperation is still lacking. Accountability is also low due to the absence of open performance reports. The lack of transparency causes residents to not know the results of the BPD's work. Therefore, the BPD needs to be more open and active in providing its performance results so that public trust and participation increase. In conclusion, the duties and functions of the Patukuki Village Consultative Body have not been running well. This is due to weak coordination with the village government and lack of community participation. Therefore, the Village Consultative Body needs to be more open and active in providing its performance results so that public trust and participation increase.